A bug, a bear, and a boy go to school - McPhail, David, 1940- (New York : Scholastic, 1999)
Despite their different sizes, a boy, a bear, and a bug enjoy themselves as they go to school, take a ride in a wagon, fly a kite, and paint a picture.
"Cartwheel books."
Preschool-grade 1
Keywords: Bears -- Juvenile fiction; Insects -- Juvenile fiction